Association of Radiotherapy-Related Intestinal Injury and Cancer-related Fatigue: A Brief Review and Commentary - Gonzalez-Mercado, Velda J.; Marrero, Sara; Pérez-Santiago, Josué; Tirado-Gómez, Maribel; Marrero-Falcón, Miguel A.; Pedro, Elsa; Saligan, Leorey N. (Puerto Rico Health Sciences Journal, 2021)
Radiotherapy treatment−induced intestinal injury and gut microbial perturbation/dysbiosis have been implicated in the pathobiology of cancer-related fatigue. The objective of this brief review was to explore the available evidence of the relationship between intestinal injury and self-reported fatigue, especially among cancer patients. The scientific evidence—including our own—linking gut mucosal barrier dysfunction and gut microbial perturbation/dysbiosis induced by cancer treatment with worsening of cancer related fatigue (perhaps through the gut-brain axis) is limited but promising. Emerging data suggest that lifestyle interventions and the administration of specific probiotics may favorably modulate the gut microbiota and potentially mediate beneficial effects leading to improvements in fatigue.